Issues and challenges in the implementation of Industrialised Building Systems in Malaysia - Abd. Rahman, Ahmad Baharuddin; Omar, Wahid (2006)

(untitled)
The Industrialized Building Systems (IBS) Roadmap 2003-2010 published by the Construction Industry Development Board (CIDB) outlines several well-thought strategies and aggressive steps to promote the use of IBS in Malaysia. The government is taking the leading role to persuade the construction industry to engage a more systematic approach and methodology in construction. It is a strategic change in the construction industry and the effort started in 1998. Besides the aim to gradually reduce the dependency on foreign labour and saves the country from losing out foreign exchange, IBS provides the opportunity for the players in the construction industry to develop a new image of the construction industry to be at par with other manufacturing industries such as car and electronic industries. With the present conventional methods of construction, the industry is always associated with many unprofessional practices. The adoption of IBS promises to elevate every level of the industry to a new height and image of professionalism. By adopting IBS, efficient, clean, safe, professionally managed and handled by professionals and workers with relevant skills, proper coordination and management, precision, innovative and quality will be appeared as new attributes to be associated with the construction industry. The industry players are expected to venture internationally and one of the pre-requisite to compete globally is to offer quality, efficient and professional services and again IBS can be an excellent option. Although some of IBS have been introduced in Malaysia as early as in 1960’s, the industry as a whole seems quite reluctant to exploit the use of IBS. A recent survey carried out on the use of IBS in Malaysia reveals some of the issues and challenges, which require attention from different parties.